Synthesis of Cellulose-Based Nanomaterials Agricultural Waste for Heavy Metal Adsorption in Water Applications - Suhdi; Setiarto Pratigto (CV. Get Press Indonesia, 2025)
Heavy metal contamination in aquatic systems drives the need for sustainable and high-performance adsorbents. This study developed functionalized nanocellulose materials derived from rice husk waste for efficient removal of Pb(II), Cd(II), Cu(II), and Cr(VI) from aqueous solutions. Cellulose nanocrystals (CNCs) were synthesized via sulfuric acid hydrolysis and functionalized through TEMPO-mediated oxidation to introduce carboxyl groups, while cellulose nanofibrils (CNFs) were modified by ethylenediamine grafting to incorporate amine functionalities. Characterization using FTIR, XRD, and SEM confirmed successful surface modification, reduced crystallinity, and the presence of nanoscale fibrillar morphologies. Batch adsorption studies showed that CNC-TEMPO achieved a maximum adsorption capacity of 189.5 mg/g for Pb(II) and 112.3 mg/g for Cd(II) at pH 5–6, while CNF-Amine exhibited superior performance for Cr(VI) removal with a capacity of 205.5 mg/g at pH 3–4. Kinetic analysis followed a pseudo-second-order model (R² > 0.99), indicating chemisorption as the dominant mechanism, whereas isotherm fitting with the Langmuir model (R² > 0.98) confirmed monolayer adsorption. The enhanced adsorption capacity was attributed to electrostatic interactions and surface complexation between functional groups (–COO⁻, –NH₂) and metal ions. These findings highlight that rice husk–derived, surface-modified nanocellulose provides a low-cost, eco-friendly, and efficient alternative for heavy metal remediation and sustainable wastewater treatment applications.